Enhancing trehalose production via Bacillus species G1 cyclodextrin glucanotransferase mutants: modifying disproportionation characteristics and thermal stability - Miao, Bobo; Huang, Di; Wang, Tengfei; Liu, Hongling; Hao, Zhifeng; Yuan, Haibo; Jiang, Yi (Frontiers in Microbiology, 2024)
Inefficient conversion of small molecule maltooligosaccharides into trehalose greatly affects the cost of the production of trehalose by double enzyme method [maltooligosyl trehalose synthase (MTSase) and maltooligosyl trehalose trehalohyrolase (MTHase)]. This study used directed evolution to increase oligosaccharide utilization by the cyclomaltodextrin glucanotransferase (CGTase) from Bacillus species G1. This enzyme was chosen for its adaptability and stability in trehalose production. Model analysis revealed that the hydrogen bond distance between the N33K mutant and maltose reduced from 2.6 Å to 2.3 Å, increasing maltose affinity and boosting transglycosylation activity by 2.1-fold compared to the wild type. Further mutations improved thermal stability and optimum temperature, resulting in the N33K/S211G mutant. Consistent results from repeated experiments showed that the N33K/S211G mutant increased trehalose yield by 32.6% using maltodextrin. The results enhanced the double-enzyme method formed by MTSase and MTHase for trehalose production. Overall, we have identified optimal catalytic conditions, demonstrating significant potential for industrial-scale trehalose production with enhanced efficiency and cost-effectiveness.